2005
DOI: 10.1038/nbt1087
|View full text |Cite
|
Sign up to set email alerts
|

Stable antibody expression at therapeutic levels using the 2A peptide

Abstract: Therapeutic monoclonal antibodies (mAbs) are currently being developed for the treatment of cancer and other diseases. Despite clinical success, widespread application of mAb therapies may be limited by manufacturing capabilities. In this paper, we describe a mAb delivery system that allows continuous production of a full-length antibody at high-concentrations in vivo after gene transfer. The mAb is expressed from a single open reading frame by linking the heavy and light chains with a 2A self-processing pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
384
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(395 citation statements)
references
References 33 publications
8
384
3
Order By: Relevance
“…All the constructs, irrelevant to the origin of 2A peptides (T2A, F2A, P2A), functioned to produce the TCR in these two cell lines as demonstrated by fluorescence-activated cell sorting (FACS) analysis following gp100 tetramer staining ( Figure 1c). In contrast to a previous report, 29 the addition of furin to the 2A peptide inhibited TCR expression, whereas furin plus the addition of spacer sequences (GSG or SGSG) enabled highly efficient gene expression (up to 95%). While active in T-cell lines, these constructs produced significantly less TCR in primary PBL (o34% tetramer+; Supplementary Figure 1).…”
Section: A Peptides Along With Furin and Spacer Facilitate Transgenecontrasting
confidence: 96%
“…All the constructs, irrelevant to the origin of 2A peptides (T2A, F2A, P2A), functioned to produce the TCR in these two cell lines as demonstrated by fluorescence-activated cell sorting (FACS) analysis following gp100 tetramer staining ( Figure 1c). In contrast to a previous report, 29 the addition of furin to the 2A peptide inhibited TCR expression, whereas furin plus the addition of spacer sequences (GSG or SGSG) enabled highly efficient gene expression (up to 95%). While active in T-cell lines, these constructs produced significantly less TCR in primary PBL (o34% tetramer+; Supplementary Figure 1).…”
Section: A Peptides Along With Furin and Spacer Facilitate Transgenecontrasting
confidence: 96%
“…This result, together with Western blot analysis, confirmed that fully assembled bioactive antibody complex was successfully produced from the IntF2A‐based polyprotein system. With the N‐extein linker‐free IntF2A system, the processed antibody light chain preserved its authentic C‐terminus without addition of any residual amino acids, which is superior to previously reported approaches (Fang et al ., 2005). The native N‐terminus of the processed downstream heavy chain fragment should also be preserved as the proline residue introduced by the action of F2A is removed upon signal peptide cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…To produce a stoichiometric amount of the heavy and light antibody chain, the effector construct was designed as a single mRNA transcript comprising coding sequences for three polypeptide chains, an anti-hTNF-a antibody heavy chain, an anti-hTNF-a antibody light chain, and hIL-1RA or mIL-10. The polypeptide-coding chains were linked through the coding sequence for the 2A peptide, which interrupts the translation of the polypeptide chain, similar as described previously 34 ( Figure 5A). These composite anti-inflammatory therapeutics were integrated in the final effector constructs pAS116 (TRE-UAS-P MIN -anti-hTNF-a Ab-hIL-1RA) and pAS134 (TRE-UAS-P MIN -anti-hTNF-a Ab-mIL-10, Table S1).…”
Section: Design and Biological Activity Of The Composite Antiinflammamentioning
confidence: 99%